Um estudo exploratório sobre o planejamento e orçamento empresarial - Souza, Claudio Peternella de (2007)
The main objective of the performance management is to optimize the business processes, aligning them to the organization strategy. Planning and Budgeting are critical in the organization performance management, because, it provides the best way to translate the strategy in a coherent set of initiatives, objectives and accomplishment means (VENTANA, 2004). In spite of the importance of the Planning and Budget, also denominated Budget Planning, this tool has been hardly criticized and questioned related to limitations, distortions, process, costs and efective results. The objective of this study is to analyze where are the organizations, actually, related to the use of the Planning and Budget as a managerial tool. This study development strategy was guided by bibliographical research where the theme was confronted with traditional and actual approaches and for a survey, with the objective of collecting evidences about the current stage of the Planning and Budget process in the organizations